Long-Acting Injectable Antipsychotics for First-Episode Schizophrenia: The Pros and Cons. (14th August 2012) - Kim, Borah; Lee, Sang-Hyuk; Yang, Yen Kuang; Park, Jong-Il; Chung, Young-Chul
Abstract : Clinical and psychosocial deterioration associated with schizophrenia occurs within the first few years following the onset of the illness. Therefore, to improve the long-term prognosis, it is important to provide schizophrenia patients with intensive treatment following their first episode. Relapse is highly associated with partial medication adherence or nonadherence in patients with first-episode schizophrenia. Recent studies suggest that long-acting injectable (LAI) antipsychotics compared with oral antipsychotics are more effective for medication adherence and relapse prevention. Moreover, some clinical guidelines for the treatment of schizophrenia suggested that LAI antipsychotics should be considered when patients are nonadherent "at any stage." Decreased compliance is a common cause of relapse during the initial stages of the disease. Therefore, LAI antipsychotics should be highly considered when treating patients with first-episode schizophrenia. In the present paper, clinical trial data and current guidelines on the use of LAI antipsychotics for first-episode schizophrenia are discussed as well as the pros and cons of this treatment option.